Vpliv mikrostrukture aluminijevih zlitin s silicijem na hrapavost površine po finem struženju - Grum, Janez (Kovine zlitine tehnologije, 1997)
Aluminium alloys can be used in a cast work, hardened or heat treated condition. Considering the facts that most products made from non-ferrous alloys are built into assemblies after their treatment, it is necessary that the microstructure condition of the alloy is considered prior to selecting the machining conditions and tool geometry. In the contribution the behaviour of the subeutectic, eutectic and supereutectic Al-alloys with silicon as well as the effects of additional alloying with different alloying elements is investigated. On the basis of judgement about microstructural components, after fine-turning notable influences of the microstructure on the occurrence of surface roughness could be found. A linear discriminating function was successfully used for predicting the expected surface roughness given that the chemical composition of the alloy was known.
Keywords: odrezavanje; struženje fino; mikrostrukture; zlitine AL; zlitine Al-Si; lastnosti zlitin; izboljšanje lastnosti; sestave kemične; zlitine; aluminij; aluminum; silicij; mikrostruktura; hrapavost; struženje